SERUM ANTIGLIADIN ANTIBODIES IN EGYPTIAN CHILDREN WITH AUTISM SPECTRUM DISORDER: RELATIONSHIP TO GASTROINTESTINAL SYMPTOMS, BEHAVIORAL AND SOCIAL COMMUNICATIONS - R El-alameey, Inas; Ahmed, Hanaa H; Eid, Ihab M; El-dory, Ghada; Gameel, Manal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Gastrointestinal symptoms are major characteristic in children with autism spectrum disorder (ASD), drawing attention to a potent association with gluten sensitivity. The goal of this study was to evaluate anti-gliadin antibodies serum levels in a group of Egyptian children with ASDs and to address the potential link to gastrointestinal (GI) symptoms, behavioral, and social communications. Patients and Methods: This descriptive caseâ€“control study included 45 children diagnosed as ASD according to Diagnostic and Statistical Manual of Mental Disorders 5th Edition and a history of GI symptoms, compared with 45 apparently healthy children of matched age and sex. Serum anti-gliadin antibodies were measured using enzyme-linked immunosorbent assay kits. Results: Serum levels of IgM, IgA, and IgG class antibodies to gliadin showed a significant increase compared to healthy controls (p<0.000). Multiple logistic regression analysis showed a significant association between the high serum levels of IgA and IgM class antibodies to gliadin in the studied patients and GI symptoms (p<0.05). A significant association was detected between the high serum levels of IgG antibodies to gliadin and the behavior symptoms (p<0.05). Conclusions: The anti-gliadin antibody response and its association with GI symptoms indicated the involvement of abnormal immunologic intestinal permeability in affected children. Immune system of some autistic patients could be abnormally triggered by gluten assumption.